Gambaran hematologi domba selama transportasi : peran multivitamin dan meniran - . Andriyanto; Yulia Suci Rahmadani; Aryani Sismin Satyaningtijas; Abadi Sutisna (Institut Pertanian Bogor, 2010)
This research was conducted to study hematological condition (total erythrocyte, concentration of haemoglobin, and packed cell valome value) sheep during transportation with combination of multivitamin-meniran. Twelve Priangan sheep were divided of into 3 groups i.e, sheep with transportation stress (control), transportation stress and multivitamin (Treatment B). The sheep were given stress transportation for 12 hours within 250 km around Bogor district. Blood samples were taken at 0 hour (pre transportation), 4h, 8h, 12h (during transportation) and 24h, 48h, 72h (post transportation) to observe total erythrocyte, concentration of haemoglobin increased and researched the peak at 8 hours although the range is still in normal condition. Packed cell volume of sheep under stress did not change. It was concluded that the combination of multivitamin-meniran was effective in maintaining haematological condition during sheep transportation.